Determination of the minimum area of sanitary landfills for use in the next 25 years in the Chapecó-SC microregion (Research, Society and Development, 2021)
This present work aimed to demonstrate a method to obtain the minimum size of a landfill based on population growth in the current scenario of economic development in Brazil. Using as methodological basis logistic curves with estimated population growth, projection of waste collected by the SGompertz model and with estimates of the production of urban solid waste (USW) of municipalities in the Chapecó microregion in the years 2021 to 2045, as a way to determine the area necessary for the final disposal of these USW, finding areas necessary for the implementation of landfills starting from 819 m² reaching approximately 500 thousand m² as in the case of Chapecó, the largest city in the region. The knowledge of the minimum landfill area is of great importance for municipalities to organize their management policies and for planning their USW policies.